MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL KOOPERATIF TEKNIK JIGSAW PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS III SEKOLAH DASAR NEGERI 3 METRO PUSAT TAHUN PELAJARAN 2014/2015 - Yuningsih Yuningsih (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2017)
This study aims to improve motivation and learning outcomes of Civics Education subjects of third grade students of Elementary School 3 Metro Center by applying cooperative model of jigsaw technique. This study uses classroom action research conducted in 2 cycles, each cycle consists of planning, implementation, observation, and reflection with data analysis techniques in the form of qualitative and quantitative analysis. The object of research is the third grade students of Elementary School Negeri 3 Metro Center as many as 25 students. The percentage of students' learning motivation in cycle I is 74,52% and cycle II is 88,74%. This shows an increase from cycle I to cycle II of 13.9%. Average student learning outcomes in cycle I of 61.2 with the percentage of students complete learning 64%, while the average cycle II of 84 with the percentage of students complete 100% learning. Teachers should always try to improve the professionalism as an educator so that the quality resulting from the learning process the better. Teachers should always try the various learning media and learning methods in accordance with the material, in order to avoid learning that keeps children because learning does not attract the attention of children.